2020
DOI: 10.48550/arxiv.2010.15595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quadratic speedup for simulating Gaussian boson sampling

Abstract: We introduce an algorithm for the classical simulation of Gaussian boson sampling that is quadratically faster than previously known methods. The complexity of the algorithm is exponential in the number of photon pairs detected, not just the number of photons, and is directly proportional to the time required to calculate a probability amplitude for a pure Gaussian state. The main innovation is to employ the Williamson decomposition to express a mixed Gaussian state as a probability distribution over pure disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…This does not diminish the experimental achievement of large-scale GBS from Zhong et al [6], which remains faster than classical methods on supercomputers, if the time required for circuit programming (or in the present case fabricating a new, fixed interferometer) is not included. However, it has previously been reported that in boson sampling with Fock state inputs, at least 50 photon events are required to extend beyond the reach of an exact classical simulation in a reasonable time-scale [9]; for collision-free GBS, this threshold has been reported as being around 100 photons [8]; we have now demonstrated that for GBS with threshold detectors, the number of correlated detector clicks should also be around 100. For GBS with PNRDs, the number of photons required to surpass this classical threshold will depend on the amount of collisions, but must be ≥ 100.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…This does not diminish the experimental achievement of large-scale GBS from Zhong et al [6], which remains faster than classical methods on supercomputers, if the time required for circuit programming (or in the present case fabricating a new, fixed interferometer) is not included. However, it has previously been reported that in boson sampling with Fock state inputs, at least 50 photon events are required to extend beyond the reach of an exact classical simulation in a reasonable time-scale [9]; for collision-free GBS, this threshold has been reported as being around 100 photons [8]; we have now demonstrated that for GBS with threshold detectors, the number of correlated detector clicks should also be around 100. For GBS with PNRDs, the number of photons required to surpass this classical threshold will depend on the amount of collisions, but must be ≥ 100.…”
Section: Discussionmentioning
confidence: 58%
“…B n is an N × N matrix, so it is considerably faster to calculate its loop hafnian compared to A n . While a realistic GBS experiment will not produce a pure state, a Gaussian mixed state can be expressed as a statistical ensemble of pure states with differing displacement vectors [8,10]; so for the purposes of a sampling algorithm, it is generally possible to randomly choose a complex displacement vector α from the correct distribution, then sample from the corresponding pure state. Hence the computational complexity of generating a sample is set by the calculation of an N × N loop hafnian, lhaf(B n ).…”
Section: Loop Hafnian Algorithmsmentioning
confidence: 99%
See 3 more Smart Citations